Peran Kebijakan Moneter Terhadap Kemampuan Perbankan Dalam Penyaluran Pembiayaan - Moch Anshori; M Alif Shofiyudin (Jurnal Ilmiah Ekonomi Islam, 2021)
The purpose of this study is to see the response of Islamic banking in Indonesia from monetary policy. This research uses quantitative methods. The data used are the 2017-2019 financial statements. The results of this study indicate that the bank is not in a financial condition. This, coupled with liquidity in banks, monetary and monetary effects will not affect financing. As for capital, monetary policy changes will affect finances.